2002
DOI: 10.1029/2001gb001635
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of suspended particulate nitrogen (δ15Nsus) in surface waters of the Atlantic Ocean from 50°N to 50°S

Abstract: [1] Isotopic composition of suspended particulate nitrogen (d 15 N sus ) has been studied in near-surface waters along a transect extending from 50°N to 50°S in the Atlantic Ocean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 62 publications
6
38
1
Order By: Relevance
“…2) were within the range (-28 to -12‰ and -1.5 to 19‰, respectively) reported in surface water at middle latitude in the northern hemisphere (Rau et al, 1982(Rau et al, , 1998(Rau et al, , 2001Saino andHattori, 1985, 1987;Altabet, 1989;Altabet et al, 1991;Saino, 1992;Goericke and Fry, 1994;Minagawa et al, 2001;Mino et al, 2002). The C/N of 5.6 to 9.9 at 0-10 m depth fell within the range of plankton of 5-12 (Tyson, 1995).…”
Section: Sediments Off Tokachisupporting
confidence: 57%
“…2) were within the range (-28 to -12‰ and -1.5 to 19‰, respectively) reported in surface water at middle latitude in the northern hemisphere (Rau et al, 1982(Rau et al, , 1998(Rau et al, , 2001Saino andHattori, 1985, 1987;Altabet, 1989;Altabet et al, 1991;Saino, 1992;Goericke and Fry, 1994;Minagawa et al, 2001;Mino et al, 2002). The C/N of 5.6 to 9.9 at 0-10 m depth fell within the range of plankton of 5-12 (Tyson, 1995).…”
Section: Sediments Off Tokachisupporting
confidence: 57%
“…This study, confined to the open ocean, revealed consistently higher δ 15 N values (by up to 5 ‰) below the surface layer and small variability with either depth or geographical location, with all values falling between 9 and 11 ‰ north of the equator. Surface-layer values were lower, but still substantially above (>6 ‰) the normal oceanic range (e.g., Altabet, 1989;Mino et al, 2002;Montoya et al, 2002). The only exception to this general trend was found in the region affected by a Trichodesmium bloom where δ 15 N fell to ∼4 ‰.…”
Section: Introductionmentioning
confidence: 89%
“…These values are the typical concentrations of organic nitrogen in oligotrophic oceans (e.g. Minagawa et al, 2001;Mino et al, 2002;Meador et al, 2007).…”
Section: Geochemical Data Analysismentioning
confidence: 98%